Estimating heat tolerance of plants by ion leakage: a new method based on gradual heating - Ilík, Petr; Špundová, Martina; Šicner, Michal; Melkovičová, Helena; Kučerová, Zuzana; Krchňák, Pavel; Fürst, Tomáš; Večeřová, Kristýna; Panzarová, Klára; Benediktyová, Zuzana; Trtílek, Martin (The New phytologist, 2018)
Heat tolerance of plants related to cell membrane thermostability is commonly estimated via the measurement of ion leakage from plant segments after defined heat treatment. To compare heat tolerance of various plants, it is crucial to select suitable heating conditions. This selection is time-consuming and optimizing the conditions for all investigated plants may even be impossible. Another problem of the method is its tendency to overestimate basal heat tolerance. Here we present an improved ion leakage method, which does not suffer from these drawbacks. It is based on gradual heating of plant segments in a water bath or algal suspensions from room temperature up to 70-75°C. The electrical conductivity of the bath/suspension, which is measured continuously during heating, abruptly increases at a certain temperature TCOND (within 55-70°C). The TCOND value can be taken as a measure of cell membrane thermostability, representing the heat tolerance of plants/organisms. Higher TCOND corresponds to higher heat tolerance (basal or acquired) connected to higher thermostability of the cell membrane, as evidenced by the common ion leakage method. The new method also enables determination of the thermostability of photochemical reactions in photosynthetic samples via the simultaneous measurement of Chl fluorescence.
Keywords: Adaptation, Physiological; Thermal Conductivity; acquired heat tolerance; heat stress; vysoká teplota; Chl fluorescence; Arabidopsis; ion leakage; Mutation; fyziologická adaptace; ionty; mutace; membrane thermostability; mastné kyseliny; basal heat tolerance; Fluorescence; Hot Temperature; heat acclimation; tepelná vodivost; Ions; fyziologický stres; Fatty Acids; Stress, Physiological; fluorescence